Association between cognition, mental health, and spirituality in elderly residents of a Long-Stay Institution (LSI) in Pernambuco (Research, Society and Development, 2024)
Objectives: Evaluate the association between cognition, mental health, and spirituality in institutionalized elderly individuals at the Abrigo Cristo Redentor (ACR) in Pernambuco. Methodology: Observational, analytical, cross-sectional, quantitative study conducted from August 2022 to August 2023. Data collection was performed through medical records and by means of the Mini-Mental State Examination (MMSE); the Geriatric Depression Scale-Short Form (GDS-SF); and the Spiritual Well-Being Scale (SWBS). The study was approved by the Research Ethics Committee under opinion 5,689,073 and followed all ethical principles of Resolution 466/10 of the National Commission for Research Ethics (CONEP). The collected data were subjected to statistical processing, using the SPSS (Statistical Package for Social Sciences) version 26. Additionally, chi-square and Fisher's exact tests were performed. In cases where the p-value was less than 0.05, the relationship between variables was considered significant. Results: The final sample consisted of 20 elderly individuals after the MMSE application, identifying those with better-preserved cognition. Among these, 6 presented mild depression, and 2 presented severe depression. All 20 elderly individuals had a moderate level of spiritual well-being, suggesting a potential association between spiritual well-being, lower depression levels, and reduced cognitive decline in the sample. Conclusion: Institutionalized elderly individuals are situated in a context of social vulnerability, which impacts cognitive impairment and depression levels. In this scenario, spirituality can be an ally.